Micro-level mechanisms of fiber waviness and wrinkling during hot drape forming of unidirectional prepreg composites. (December 2017) - Farnand, K.; Zobeiry, N.; Poursartip, A.; Fernlund, G.
Abstract: Fiber misalignment in composites in the form of in-plane waviness and out of-plane wrinkling, is a major defect arising from processes such as hot drape forming. This work studies the micro-level mechanisms of forming in-plane fiber waviness and out-of-plane wrinkling. An out-of-autoclave unidirectional prepreg system by SOLVAY (CYTEC), CYCOM 5320/T650-35 was used to conduct multiple forming experiments and study the effects of various parameters including forming temperate and lay-up sequence. The effect of partial impregnation, or 'Engineered Vacuum Channels', in out-of-autoclave prepreg systems on the intra-ply separation/slippage and consequently fiber misalignment was studied and found to be a significant contributor to micro-level mechanisms. Cross sectioning and microscopy of the parts and examination of the end termination profiles were used to analyze the effect of forming parameters on ply end-shortening and consequently fiber misalignment.